Selective Binding of Endostatin Peptide 4 to Recombinant VEGF Receptor 3 In Vitro - Han, Kyu-Yeon; Chang, Michael; Ying, Hong-Yu; Lee, Hyun; Huang, Yu-hui; Chang, Jin-Hong; T. Azar, Dimitri (Protein and Peptide Letters, 2015)
We previously reported that neostatin, a proteolytic fragment of collagen XVIII that includes endostatin, inhibits basic fibroblast growth factor-induced corneal angiogenesis and lymphangiogenesis. In experiments to determine which fragments in neostatin are responsible for binding to VEGF receptors (VEGFRs), we previously showed that a 28- mer sequence at the C-terminal of endostatin, known as endostatin peptide 9, preferentially binds VEGFR3-Fc over VEGFR1-Fc and VEGFR2-Fc. In the present study, we show that a different endostatin fragment, endostatin peptide 4 (26 mers long), also selectively binds VEGFR3-Fc and not VEGFR1-Fc or VEGFR2-Fc. From surface plasmon resonance data, the KD and Chi2 (RU2) values for endostatin peptide 4 binding to VEGFR3-Fc are 5.72x10-8 M and 0.354, respectively. In conclusion, endostatin peptides 4 and 9 may be responsible for endostatin binding to VEGFR3-Fc, and this improved understanding of endostatin peptide binding to VEGFR3-Fc may support the development of therapeutics targeting lymphangiogenic processes.
Keywords: endostatin